Trauma, memory and silence of the Irish woman in contemporary literature
1 online resource (xviii, 203 pages).
Keywords: "This volume studies the manifestations of female trauma through the exploration of multiple wounds, inflicted on both body and mind (Caruth 1996, 3) and the soul of Irish women from Northern Ireland and the Republic within a contemporary context, and in literary works written at the turn of the twenty-first century and beyond. These artistic manifestations connect tradition and modernity, debunk myths, break the silence with the exposure of uncomfortable realities, dismantle stereotypes and reflect reality with precision. Women's issues and female experiences depicted in contemporary fiction may provide an explanation for past and present gender dynamics, revealing a pathway for further renegotiation of gender roles and the achievement of equilibrium and equality between sexes. These works might help to seal and heal wounds both old and new and offer solutions to the quandaries of tomorrow"--